The use of skimming and scanning for the development of reading comprehension in english language - Ramón Ochoa, Melissa Gabriela; Herrera Morocho, Astrid Carolina (Machala: Universidad Técnica de Machala, 2023)
The aim of this research was to develop a system of activities through the use of skimming and scanning as techniques for the development of reading comprehension in English language of students of first semester of the career of Pedagogy of National and Foreign Languages of the Technical University of Machala. These techniques involve a quick reading to obtain specific information or a general idea, therefore, their development is useful in the teaching-learning process, being the reading comprehension techniques the field of this research. Two instruments are used to evaluate the reading comprehension level of 35 students, by means of a pre-test and a post-test. The results obtained showed that a considerable number of students have difficulties, due to the fact that they do not read in their mother tongue and therefore find it difficult to master it in a second language, causing a lack of reading comprehension, the latter being one of the fundamental skills when learning English. In the pre-test, 20 students were perceived as having a non-compliant level, but in the post-test the result was positive as the number of students at this level decreased, improving their reading comprehension skills. Therefore, it is concluded that the system of activities through the use of skimming and scanning as techniques for the development of English reading comprehension not only has a significant influence on the students, but will serve as tools in the process of teaching and learning English
Keywords: READING; COMPREHENSION; TECHNIQUES; ACTIVITY SYSTEM